The quickening : creation and community at the ends of the Earth - Rush, Elizabeth A. (Milkweed Editions, 2023)
"An astonishing, vital book about Antarctica, climate change, and motherhood from the author of Rising, finalist for the Pulitzer Prize in General Nonfiction"--